2022
DOI: 10.1016/j.crfs.2021.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the phenolic enriched fractions from Nixtamalization wastewater (Nejayote) fractionated in a three-step membrane process

Abstract: Nejayote is recognized as the main by-product resulting from the nixtamalization process of maize kernels, which is categorized as an alkaline residue with a chemical composition based on carbohydrates (37.8–55.7%), fiber (22.8–25.5%), protein (4.9–7.4%), and lipids (0.4–1.5%). In addition, Nejayote has an extensive content of simple (e.g., phenolic acids) and complex phenolic compounds (e.g., anthocyanins), which are responsible for the pigmentation and antioxidant activity of maize; therefore, there is a nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The judicious concentration of carotenoids through nanofiltration enables meticulous control over color attributes, facilitating the fabrication of visually captivating foods without the reliance on synthetic colorants. Furthermore, the antioxidant potential inherent in specific carotenoids contributes substantively to the overall oxidative stability of lipid-laden food formulations [14].…”
Section: Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The judicious concentration of carotenoids through nanofiltration enables meticulous control over color attributes, facilitating the fabrication of visually captivating foods without the reliance on synthetic colorants. Furthermore, the antioxidant potential inherent in specific carotenoids contributes substantively to the overall oxidative stability of lipid-laden food formulations [14].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Phenolic fractions, exhibiting anti-inflammatory, antimicrobial, and potentially anticancer attributes, have emerged as pivotal constituents in the synthesis of functional foods or pharmaceutical formulations. Meanwhile, carotenoids, acknowledged for their cutaneous health benefits and free-radicalquenching capabilities, are habitually incorporated into cosmetic formulations for skincare products [14].…”
Section: Flavonoidsmentioning
confidence: 99%
“…Phenolic compounds‐rich potato peels can be used in developing bioactive films with improved antioxidant activity, and mechanical strength (Zhao & Saldaña, 2019). Antioxidant‐rich phenolic compounds (p‐coumaric acids, ferulic acids and their derivatives) extracted from maize by‐products can be used as an enricher in functional foods with an additional nanofiltration process (Díaz‐Montes & Castro‐Muñoz, 2022).…”
Section: Food Processing Wastes and By‐products From Industriesmentioning
confidence: 99%
“…In addition, the study also showed the various influencing factors of PEF (electric field intensity, solvent type and pulse number), HVED (time, solvent and frequency) and UAE (temperature, solvent and time) on anthocyanin extraction. As of now, the extracted anthocyanin is used as natural pigment in food, and colour indicator in intelligent packaging and gelatin films (Rawdkuen et al ., 2020; Fei et al ., 2021; Díaz‐Montes & Castro‐Muñoz, 2022) Therefore, PEF‐extracted anthocyanin can also be used in the same way.…”
Section: Food Processing Wastes and By‐products From Industriesmentioning
confidence: 99%
“…In Latin America, where nixtamalized products are regarded as an absolute necessity, this by-product is produced in significant quantities due to the high demand for it. The conventional nixtamalization method requires as much as 7.5 L of water per kilogram of maize, which leads to the formation of nejayote [8]. This wastewater causes an environmental problem due to its alkalinity and biological demand for oxygen (DBO).…”
Section: Introductionmentioning
confidence: 99%